Shiloh : Shiloh #1 - Naylor, Phyllis Reynolds ([Place of publication not identified] : Atheneum, 1991)
When he finds a lost beagle in the hills behind his West Virginia home, Marty tries to hide it from his family and the dog's real owner, a mean-spirited man known to shoot deer out of season and to mistreat his dogs.
Accelerated Reader
Keywords: Dogs -- Fiction; Animal welfare -- Fiction; West Virginia -- Fiction